ENHANCING COMMUNITY KNOWLEDGE AND SELF-EFFICACY IN HYPERTENSION PREVENTION THROUGH HERBAL EDUCATION PROGRAM - Dewi Susanti Atmaja; Darini Kurniawati; Muhammad Akhzani Fadhli; Damayanti Damayanti; Indah Husnul Khatimah; Melinda Dian Puspita; Synthia Sifra Lorenza (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2026)
Introduction: Hypertension is a major public health problem and often called a “silent killer” because it can cause serious complications without early symptoms. Community knowledge about prevention and management remains limited, especially in urban areas. This activity aimed to increase public knowledge about hypertension and to introduce the use of celery leaves (Apium graveolens L.) as a complementary herbal therapy. Methods: The community service activity was carried out in Kampung Ketupat, involving 20 residents. The program included lectures, distribution of educational leaflets, and demonstration of celery juice preparation. Knowledge improvement was assessed through discussions and active participation during the session. Results: Participants showed increased understanding of hypertension and expressed strong enthusiasm in learning about herbal management. The demonstration of celery juice preparation was well received, and participants reported confidence to replicate the practice at home. Conclusion: Health education on herbal management successfully improved public knowledge and self-efficacy of hypertension prevention and control. Celery juice was accepted as an easily applicable complementary method in daily life. KEYWORDS education; herbal; hypertension; prevention